2021
DOI: 10.1002/vms3.633
|View full text |Cite
|
Sign up to set email alerts
|

Serum IL‐6 and MCP‐1 concentrations in dogs with lymphoma before and after doxorubicin treatment as a potential marker of cellular senescence

Abstract: Background: Chemotherapy can induce cellular senescence and a secretory phenotype characterized by an increased expression of inflammatory cytokines, such as IL-6 and MCP-1. Increased IL-6 and MCP-1 serum concentrations have been documented in dogs with lymphoma, but no studies have evaluated the effects of chemotherapy on cytokine concentrations.Objectives: To measure IL-6 and MCP-1 in 16 client-owned dogs with lymphoma, at baseline and before and after doxorubicin, as a potential marker for senescence and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 59 publications
(122 reference statements)
0
2
0
Order By: Relevance
“…For example, TGF-β has been demonstrated to induce senescence and senescence-related characteristics in fibroblasts [ 39 ]. Similarly, MCP has been shown to be a SASP-related protein [ 40 ]. We found significantly elevated Mmp3 , Mmp9 , Mcp , and TGF-β mRNA levels in chronic wounds ( Figure 1F ), potentially contributing to the increased senescent cell abundance in chronic wounds.…”
Section: Resultsmentioning
confidence: 99%
“…For example, TGF-β has been demonstrated to induce senescence and senescence-related characteristics in fibroblasts [ 39 ]. Similarly, MCP has been shown to be a SASP-related protein [ 40 ]. We found significantly elevated Mmp3 , Mmp9 , Mcp , and TGF-β mRNA levels in chronic wounds ( Figure 1F ), potentially contributing to the increased senescent cell abundance in chronic wounds.…”
Section: Resultsmentioning
confidence: 99%
“…In the current research, DOX administration in HCC bearing rats induced insignificant reduction in serum CCL2 level paralleled by insignificant down-regulation in CCL2 gene expression level in the liver. Evans et al (2022) demonstrated a significant increase in CCl2 (MCP-1) serum cytokine concentration at 24 h and a significant decrease at 1 week past DOX when compared to the 0-to 6 h time point. Comparing 24 h and 1 week post DOX, there was a significant decrease in CCL2 (MCP-1) cytokine concentrations in dogs with lymphoma.…”
Section: Discussionmentioning
confidence: 95%